2016
DOI: 10.1016/j.apenergy.2016.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of the thermal mechanics of lithium-ion battery cells

Abstract: h i g h l i g h t sThermal swelling shape is different than Li-ion intercalation swelling shape. Nonuniform temperature and gap creation leads to a convex shape at free conditions. Important parameters of thermal mechanics are estimated through experiments. A coupled thermal-structural analysis accurately predicts thermal swelling shape. Nonuniform temperature still plays a critical role at pack conditions. Keywords:Lithium-ion battery Battery swelling shape Thermal expansion The coefficient of thermal expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 110 publications
(142 reference statements)
0
15
0
Order By: Relevance
“…Bandhauer et al utilized a passive liquid‐vapor phase change heat removal inside micro‐channels embedded into the cell to demonstrate the possible performance improvement based on a 3D electrochemical‐thermal model. Figure shows the maximum temperature rise and difference for the internal cooling simulations as compared with the traditional air and liquid cooling reports in Bandhauer et al Based on the three‐dimensional thermal swelling model with coupled thermo‐mechanical, Oh and Epureanu indicated the elevated core temperature and uneven temperature distributions play a vital role in the performance of the battery pack. This model is beneficial to the design thermal management of battery packs, as well as the development of stress‐strain sensors and the optimal configuration.…”
Section: Model‐based Bms Applicationmentioning
confidence: 97%
“…Bandhauer et al utilized a passive liquid‐vapor phase change heat removal inside micro‐channels embedded into the cell to demonstrate the possible performance improvement based on a 3D electrochemical‐thermal model. Figure shows the maximum temperature rise and difference for the internal cooling simulations as compared with the traditional air and liquid cooling reports in Bandhauer et al Based on the three‐dimensional thermal swelling model with coupled thermo‐mechanical, Oh and Epureanu indicated the elevated core temperature and uneven temperature distributions play a vital role in the performance of the battery pack. This model is beneficial to the design thermal management of battery packs, as well as the development of stress‐strain sensors and the optimal configuration.…”
Section: Model‐based Bms Applicationmentioning
confidence: 97%
“…The positive electrode and negative electrode are coated on aluminum foil and copper foil, respectively, and entire LIPB structure is wrapped by aluminum plastic soft casing. The main problem of LIPB in engineering application is that a moving battery sustains a variety of quasi‐static or dynamic loadings and these loadings could easily cause serious consequence, such as capacity and property degradation, ISC, fire, and even severe explosion . The resistance exterior force property of LIPB represents the ability to resist the exterior loading (quasi‐static or dynamic loadings).…”
Section: Introductionmentioning
confidence: 99%
“…The main problem of LIPB in engineering application is that a moving battery sustains a variety of quasi-static or dynamic loadings and these loadings could easily cause serious consequence, such as capacity and property degradation, 8,9 ISC, fire, and even severe explosion. 2,[10][11][12][13][14] The resistance exterior force property of LIPB represents the ability to resist the exterior loading (quasi-static or dynamic loadings). And it is an important indicator for design specification and battery analysis and it directly reflects the safety and reliability of battery.…”
Section: Introductionmentioning
confidence: 99%
“…MuKai et al [60] validated that lithium manganese oxide spinels had average coefficients of volumetric thermal expansion by the maximum value of 2.39 × 10 −5 K −1 with X-ray diffraction measurements performed in the temperature range from 100 to 400 K. Because of thermal expansion of cathode, anode, and separator in a cell, Oh and Epureanu [61] found a 5Ah NMC cathode Li-ion cell swelling linearly in the through plane from 25 to 45 • C. Stress generation of a NMC cathode battery stack caused by temperature has been measured by Mohan et al [62], who found the bulky force at the battery stack surface increase with temperature rising from −5 to 45 • C at the same SOC level.…”
Section: Other Factorsmentioning
confidence: 99%
“…Although the availability of published data from in situ electrode stress/strain measurements is limited, factors that influence electrode stress generation also include the effects due to thermal expansion/contraction [60][61][62] and gas generation originated from electrochemical decomposition of electrolyte solvents by the SEI layer formation, high temperature operation, and overcharge [63][64][65]. The winding process of electrodes is the important production technique for Li-ion battery fabrication [66], which can also cause electrode stress generation from external forces and body forces.…”
Section: Other Factorsmentioning
confidence: 99%